Cortical Thickness Alterations in Patients With Tinnitus Before and After Sound Therapy: A Surface-Based Morphometry Study - Wei, Xuan; Lv, Han; Chen, Qian; Wang, Zhaodi; Liu, Chunli; Zhao, Pengfei; Gong, Shusheng; Yang, Zhenghan; Wang, Zhenchang (Frontiers in Neuroscience, 2021)
This study aimed to explore brain surface-based morphometry cortical thickness changes in patients with idiopathic tinnitus from before to after 24 weeks of sound therapy. Thirty-three tinnitus patients underwent magnetic resonance imaging at baseline and after 24 weeks of sound therapy. Twenty-six age- and sex-matched healthy control (HC) individuals also underwent two scans over a 24-week interval. A 3D-BRAVO pulse sequence was used to acquire 3.0T MRI and high-resolution 3D structural images. Structural image data preprocessing was performed using the DPABISurf toolbox. Tinnitus Handicap Inventory (THI) scores were acquired in the tinnitus group to assess the severity of tinnitus and tinnitus-related distress. Two-way mixed model analysis of variance (ANOVA) and Pearson’s correlation analysis were used in the statistical analysis. Student-Newman-Keuls (SNK) tests were used in the post hoc analysis. Significantly lower cortical thickness was found in the left somatosensory and motor (SMC), left posterior cingulate cortex (PCC) and right orbital and polar frontal cortex (OPFC) of the participants in the tinnitus group at baseline than in the participants in the HC group at baseline and after 24 weeks; the 24-week sound therapy tinnitus group had a significantly higher cortical thickness in the left SMC, bilateral superior parietal cortex (SPC), left inferior parietal cortex (IPC), left PCC and right OPFC than the tinnitus baseline group; the tinnitus sound therapy group had slightly lower cortical thickness in the bilateral SMC, bilateral SPC, right OPFC, left IPC and left PCC than the HC baseline group and the HC 24-week group, although these differences did not reach statistical significance. There were no significant differences in the bilateral paracentral lobular and midcingulate cortex (PCL&MCC), left dorsal stream visual cortex (DSVC) or left primary visual cortex (PVC) in post hoc analysis. The changes in cortical thickness before and after sound therapy can provide certain reference value for clinical tinnitus treatment. These brain regions could serve as potential targets for neuroimaging.